APPLICATION OF SANCTIONS FOR THE COMMUNITY FOR THE FORCED RETRIEVAL OF BODIES COVID-19 BASED ON THE POLICE CHIEF'S TELEGRAM NUMBER ST/1618/VI/OPS.2/2020 IN THE POLICE DEPARTMENT NORTH SUMATRA REGION - Maysarah Maysarah; Fadhil Yazid; Dody Safnul (Dharmawangsa: International Journal of the Social Sciences, Education and Humanitis, 2021)
ABSTRACTIn North Sumatra, as of December 2020 there are ± 16,174 Covid-19 cases, with the number of deaths due to Covid-19 in North Sumatra reaching ± 632 people. In North Sumatra, cases of forced retrieval of Covid-19 bodies occurred in several hospitals, including Madani Hospital, Pirngadi, Murni Teguh and Royal Prima. In the case of the number of cases of forced retrieval of patient bodies under Covid-19 supervision by families in various regions in Indonesia prompted the Indonesian Police to issue a telegram letter of the Chief of Police Number ST/1618/VI/Ops.2/2020. The research method used in this research is to combine library research with field research. The result of this study is that if there is a party that performs forced retrieval of Covid-19 patients' bodies in accordance with applicable procedures, it may be subject to criminal sanctions. The legal basis is Article 5 of Law Number 4 Year 1984 concerning Infectious Disease Outbreaks with the threat of one year in prison or a fine of up to Rp. 100 million as stipulated in Article 93 of Law Number 6 Year 2018 concerning Health Quarantine. In addition, parties who take the bodies of Covid-19 patients by force can also be subject to layered Article 212 of the Criminal Code jo Article 214 of the Criminal Code jo Article 216 of the Criminal Code jo Article 335 of the Criminal Code jo Article 336 of the Criminal Code jo Article 93 of Law Number 6 of 2018, with the threat of punishment of up to 7 (seven) years.Keywords : Forced Retrieval , Covid 19 Corpse , The Police Chief's Telegram, North Sumatra